Application of total error concept in the analytical method validation for the assay of essential amino acids by precolumn derivatization - Ramachandra Reddy Aasodi, Murugan V, Premakumari KB (Journal of Applied Pharmaceutical Science, 2020)
A pre-Ultraperformance Liquid Chromatography (UPLC) column derivatization procedure was developed for the simultaneous quantification of essential amino acids (EAAs) in the solid oral dosage pharmaceutical formulation. This analytical procedure has been validated with the help of the concept of total error. The total error approach (the combination of systematic and random error) is a decision-making tool for ensuring the performance of the method. Fluorenylmethyloxycarbonyl chloride was used as a derivatization reagent. The amino acid derivatives were separated on a C18 column (internal diameter 2.1 × 100 mm, 1.6 μm) by gradient elution with 0.1% trifluoroacetic acid and acetonitrile:water (90:10, v/v), respectively, as mobile phase A and B. About 10 EAAs could be detected at 265 nm in 35 minutes with a flow rate of 0.25 ml/min. The linearity range of each amino acid was between 0.1 and 1.0 mg/ml. The accuracy and risk profiles were considered acceptable across the range. The precolumn derivatization procedure and the concept of the validation of total error could be used as an appropriate strategy to demonstrate the suitability of the analytical procedure for the separation and evaluation of EAA in solid oral dosage formulations.
Keywords: Essential amino acids, pre-column derivatization, total error, UPLC, accuracy profile.